2018
DOI: 10.1177/0284185118780906
|View full text |Cite
|
Sign up to set email alerts
|

Application of MRS- and ASL-guided navigation for biopsy of intracranial tumors

Abstract: Background The diagnosis of a tumor depends on accurate identification of the target area for biopsy. However, tumor heterogeneity and the inability of conventional structural data for identifying the most malignant areas can reduce this accuracy. Purpose To evaluate the feasibility and practicality of magnetic resonance spectroscopy (MRS)- and arterial spin labeling (ASL)-guided MRI navigation for needle biopsy of intracranial tumors. Material and Methods Thirty patients with intracranial tumors who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Teng et al showed that glioma puncture guided by 3D-ASL had a higher success rate than conventional MRI. In this study, 6 cases of low-enhancing or non-enhancing gliomas were successfully punctured, indicating that 3D-ASL has great potential in guiding the determination of tumor targets for NE-LGGs [9]. 3D-ASL is widely used in the diagnosis, grading and e cacy evaluation of gliomas [8, 10,11], while its application in guiding NE-LGG radiotherapy has rarely been reported.…”
Section: Introductionmentioning
confidence: 93%
“…Teng et al showed that glioma puncture guided by 3D-ASL had a higher success rate than conventional MRI. In this study, 6 cases of low-enhancing or non-enhancing gliomas were successfully punctured, indicating that 3D-ASL has great potential in guiding the determination of tumor targets for NE-LGGs [9]. 3D-ASL is widely used in the diagnosis, grading and e cacy evaluation of gliomas [8, 10,11], while its application in guiding NE-LGG radiotherapy has rarely been reported.…”
Section: Introductionmentioning
confidence: 93%
“…In a biopsy study, ASL guidance was found to improve the accuracy of target selection for stereotaxic biopsies when combined with MRS [ 55 ]. A conclusive diagnosis could be made for 28 out of 30 patients (93.3%).…”
Section: Angiogenesismentioning
confidence: 99%
“…There is substantial risk of inaccuracy in stereotactic biopsy, with under-grading of WHO grade III tumours reported in 28% of cases [26]. The successful stereotactic biopsy diagnosis rate utilising multiparametric MRI techniques has shown to be more than 93% [27]. To get a .…”
Section: Targeting Biopsy For a Non-enhancing Tumourmentioning
confidence: 99%
“…There is substantial risk of inaccuracy in stereotactic biopsy, with under-grading of WHO grade III tumours reported in 28% of cases [ 26 ]. The successful stereotactic biopsy diagnosis rate utilising multiparametric MRI techniques has shown to be more than 93% [ 27 ]. To get a better biopsy yield and to avoid sampling error for non-enhancing tumours, the target of biopsy can be selected from a high choline, high rCBV or low ADC location.…”
Section: Neoplastic Lesionsmentioning
confidence: 99%